The impact of cesarean section on neonatal outcomes at a university-based tertiary hospital in Jordan - Wasim Khasawneh; Nail Obeidat; Dawood Yusef; Jomana W. Alsulaiman (BMC, 2020)
Abstract Background Over the past two decades, there has been a steady rise in the rate of Cesarean section delivery globally. As a result, short-term and long-term maternal and neonatal complications are rising. The objective of this study is to determine the rate and indications for Cesarean section at King Abdullah University Hospital (KAUH) in Jordan and to assess the resulting neonatal outcomes. Methods A retrospective chart review was conducted for all women and neonates delivered by Cesarean section during the period January 2016 to July 2017 at KAUH tertiary academic center. Collected data include demographic characteristics, indication for delivery, and neonatal outcomes such as NICU admission, respiratory complications, sepsis, mortality, and length of hospitalization. Results Two thousand five hundred ninety-five Cesarean section deliveries were performed over 18 months representing a rate of 50.5% of all deliveries. Sixty percent were scheduled procedures. Seventy-two percent were performed at full term gestation. The most common indication was previously scarred uterus (42.8%) followed by fetal distress (15.5%). The rate of admission to the neonatal ICU was 30% (800/2595). After multilogistic conditional regression analysis, the factors associated with increased risk of neonatal ICU admission were found to include grandmultiparity (Adjusted OR 1.46), gestational diabetes (Adjusted OR 1.92), maternal employment (Adjusted OR 1.84), prolonged rupture of membranes (Adjusted OR 5), fetal distress (Adjusted OR 1.84), prematurity (Adjusted OR 43.78), low birth weight (Adjusted OR 42), high order multiple gestation (Adjusted OR 9.58) and low 5-min APGAR score (Adjusted OR 10). Among the babies electively delivered at early term (37-38.6 weeks), 16% were admitted to the NICU for a median length of stay of 4 days (IQR 2, 8). The most common diagnoses for admitted term neonates were transient tachypnea of newborns and respiratory distress syndrome. Conclusions CS deliveries account for more than half the number of deliveries at our institution and almost one third of the delivered babies are admitted to the NICU. Together with the resulting maternal and neonatal consequences, this carries a major burden on the newborns, health care facilities, and involved families. Local strategies and policies should be established and implemented to improve the outcome of births.